Al-Ghazali's Views On The Economy And Development Of The Ummah - Nurlinda (PT. Islamic Research Publisher, 2023)
This study examines the thoughts of Al-Ghazali who is one of the great thinkers in Islamic economics. Because according to him economic development as part of the tasks of social obligations set by God. In his works Al-Ghazali emphasized justice, peace and stability as the foundation of economic availability in the fields of production, consumption and distribution. For that, the role of the state is very important to maintain it all. Penelitian This study describes the thoughts of Imam Al-Ghazali in the field of economics which is used as the principle and basic benchmark of Islamic economics. This study aims to find out how the biography of Al-Ghazali, the works of Al-Ghazali, pandangan Al-Ghazali views on the economy and development of the Ummah. In this study, researchers use normative legal research that we know as research law literature that is legal articles conducted by researching based on materials sourced from the library. Sources of data obtained are taken from books, journals, and sumber-sumber other sources on the issues yang discussed , namely about Al-Ghazali's views on the economy and development of the Ummah. The results showed that economic activities must be in accordance with Islamic law for the benefit. In addition, in the book Ihya Ulumuddin there are several konsep economic concepts yang offered by Al-Ghazali, among others; the concept kesejahteraan of social welfare (maslahah), Pertukaran voluntary exchange and the evolution of the market, Etika Market Ethics, Aktivitas production activities, Barter and the evolution of money, the role of the state and Keuangan Public Finance